2018
DOI: 10.1016/j.neuron.2018.07.009
|View full text |Cite
|
Sign up to set email alerts
|

The Role of m6A/m-RNA Methylation in Stress Response Regulation

Abstract: SummaryN6-methyladenosine (m6A) and N6,2′-O-dimethyladenosine (m6Am) are abundant mRNA modifications that regulate transcript processing and translation. The role of both, here termed m6A/m, in the stress response in the adult brain in vivo is currently unknown. Here, we provide a detailed analysis of the stress epitranscriptome using m6A/m-seq, global and gene-specific m6A/m measurements. We show that stress exposure and glucocorticoids region and time specifically alter m6A/m and its regulatory network. We d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
295
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 316 publications
(328 citation statements)
references
References 70 publications
15
295
1
1
Order By: Relevance
“…4–5 m 6 A modifications per 1000 adenosine nucleotides) in Arabidopsis and cauliflower mitochondria, respectively (Table S2). Analyses of the relative m 6 A levels using calorimetric measurements have been previously shown to be well correlated with those of liquid MS/MS analyses (Slobodin et al , ; Engel et al , ). The data were also in agreement with previous reports by Luo et al () and Wang et al (), which suggested that the extent of m 6 A modifications in Arabidopsis organelles (i.e.…”
Section: Resultsmentioning
confidence: 90%
“…4–5 m 6 A modifications per 1000 adenosine nucleotides) in Arabidopsis and cauliflower mitochondria, respectively (Table S2). Analyses of the relative m 6 A levels using calorimetric measurements have been previously shown to be well correlated with those of liquid MS/MS analyses (Slobodin et al , ; Engel et al , ). The data were also in agreement with previous reports by Luo et al () and Wang et al (), which suggested that the extent of m 6 A modifications in Arabidopsis organelles (i.e.…”
Section: Resultsmentioning
confidence: 90%
“…Inaccuracy, failure, or misuse of each of these pathways can trigger very different consequences on the genome. DSB repair pathway choice can be influenced by cell cycle phase (Hustedt and Durocher, 2016), DNA end complexity (Schipler and Iliakis, 2013), and the type of damaged locus (Clouaire and Legube, 2015, Engel et al., 2018). …”
Section: Introductionmentioning
confidence: 99%
“…Increasing evidence suggests a central role of m 6 A during nervous system development and functions (Angelova et al, 2018;Du et al, 2019;Jung and Goldman, 2018;Li et al, 2019;Livneh et al, 2020;Widagdo and Anggono, 2018). m 6 A is present at particularly high levels in the nervous system of different model animals (Lence et al, 2016;Meyer et al, 2012), and these levels can vary following behavioral stimuli or sensory experience (Engel et al, 2018;Koranda et al, 2018;Widagdo et al, 2016;Yoon et al, 2018). In mouse, m 6 A controls brain development Li et al, 2017;Li et al, 2018;Ma et al, 2018;Wang et al, 2018;Zhuang et al, 2019) and is also required for axon regeneration and synaptic functions (Engel et al, 2018;Koranda et al, 2018;Merkurjev et al, 2018;Shi et al, 2018;Yu et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…m 6 A is present at particularly high levels in the nervous system of different model animals (Lence et al, 2016;Meyer et al, 2012), and these levels can vary following behavioral stimuli or sensory experience (Engel et al, 2018;Koranda et al, 2018;Widagdo et al, 2016;Yoon et al, 2018). In mouse, m 6 A controls brain development Li et al, 2017;Li et al, 2018;Ma et al, 2018;Wang et al, 2018;Zhuang et al, 2019) and is also required for axon regeneration and synaptic functions (Engel et al, 2018;Koranda et al, 2018;Merkurjev et al, 2018;Shi et al, 2018;Yu et al, 2018). Similarly, in Drosophila, m 6 A promotes flight and locomotion via a neuronal function (Haussmann et al, 2016;Kan et al, 2017;Lence et al, 2016;Lence et al, 2017).…”
Section: Introductionmentioning
confidence: 99%